Analisis Implementasi Kebijakan Penghapusan Denda Pajak Kendaraan Bermotor Dalam Upaya Meningkatkan Penerimaan Pajak Kendaraan Bermotor Tahun 2018-2020 Di Kantor Samsat Jakarta Timur - Norma Suryani; Tri Djoko Hardjono (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This study aims to analyze the implementation of motor vehicle tax fines elimination policy in an effort to improve on 2018-2020 motor vehicle tax revenues at the SAMSAT office of East Jakarta, and identify that support and hinder the implementation of the policy. This research uses descriptive qualitative method. The data used in this study include primary data obtained from informant interviews and secondary data. Data was collected through interviews and documentation. The results showed that the implementation of motor vehicle tax penalty elimination policy at the East Jakarta SAMSAT office in 2018-2020 was quite effective because motor vehicle tax revenues were always increasing since. This is supported by several driving entities such as the campaign carried out by SAMSAT and relevant agencies such as the police, insurance company Jasa Raharja and Data and Information Center, and the Information and Statistics Communications Sub-dept., and the installation of banners through print and internet media so that the public is aware of the policy. However, there are still obstacles in its implementation, such as inadequate facilities and infrastructure to accommodate the number of taxpayers who want to pay taxes when the motor vehicle tax penalties are eliminated